Natural Frequency of Tension Cable Based on Moment Inertia to Span Ratio: Determination Using Analytical, Numerical and Experimental Study - Guntur Nugroho (International Journal of Sustainable Construction Engineering and Technology, 2020)
Health monitoring using vibration technique is usually conducted on cable structure. The hanger cable on the suspension bridge has a difference of span. To predict axial force of cable, the beam-string theory includes a parameter of bending stiffness. However, string theory has neglected the effect of bending stiffness. The shorter the span of the cable the greater the effect of the bending stiffness would be. This paper raises parameter moment of inertia to span ratio (I/L) to determine the apropriate analytical formula between string and beam-string. Experimental research was conducted using a vibration technique. The specimens use solid cylindrical steel beam, having length specimens of 2 m, hinge-hinge of boundary condition, and difference variations I/L of 0.024, 0.08, 0.58, 1.53 and 10.22. Numerical analysis was simulated by using Abaqus software v 6.13. The result shows that the ratio of I/L equally lowers than 0.082 has close to the analytical string theory. The ratio of I/L greather than 0.082 has close to the beam string theory.